Mixture tetracycline citric acid and detergent – A root canal irrigant. A review - G.P.V. Srikumar; K.S. Sekhar; K.G. Nischith (Journal of Oral Biology and Craniofacial Research)
Background: Root canal irrigants play an indispensable role for the complete disinfection of the root canal system, in particular those areas of the root canal that are not accessible for instrumentation. Sodium hypochlorite, ethylene diamine tetra acetic acid, hydrogen peroxide and chlorhexidine are the most commonly used root canal irrigants in endodontic practice, but they do not satisfy all the properties of an ideal root canal irrigant. Mixture tetracycline, citric acid and detergent, a root canal irrigant, is commercially available as BioPure MTAD (Dentsply, Tulsa Dental, Tulsa, OK). Methodology: The literature was searched for root canal irrigants used in the last 3 decades in PubMed. Data showed 83 relevant articles, of which 24 were found most suitable on the basis of description of properties, advantages and disadvantages of MTAD, hence were included. The aim of this study was to evaluate the properties of MTAD for its antibacterial efficiency, biocompatibility, chelating action with removal of endodontic smear layer and compare it with other commonly used root canal irrigants like sodium hypochlorite, ethylene diamine tetra acetic acid, hydrogen peroxide, chlorhexidine. Results: MTAD was found to be highly effective intracanal irrigant compared to other commonly used root canal irrigants with excellent disinfection of the entire root canal system. Conclusion: MTAD is biocompatible with superior antimicrobial efficiency compared to other commonly used root canal irrigants.